Analisis Akad Murabahah pada Produk Pembiayaan Cicilan Emas di PT Bank Syariah Indonesia Kantor Cabang Pasuruan: Tinjauan Kepatuhan Syariah Berdasarkan Fatwa DSN-MUI No. 77/2010 - Liatul Aini; Saiful Bakhri (Al-Ujrah | Jurnal Ekonomi Syariah, 2025)
This study analyzes the implementation of the murabahah contract on gold installment financing products at PT Bank Syariah Indonesia (BSI) Pasuruan Branch Office. The research focuses on evaluating the conformity of the financing mechanism with sharia principles, especially regarding price determination, margin transparency, and the requirement of bank ownership over the gold before resale to customers. The analysis is based on the provisions of DSN-MUI Fatwa No. 77/DSN-MUI/VI/2010, which regulates non-cash gold transactions to prevent elements of riba, gharar, and speculation. The results indicate that the administrative procedures, financing requirements, and installment schemes implemented by BSI have fulfilled sharia compliance and operational standards. However, the study also finds challenges such as customers' limited understanding of the murabahah structure and margin mechanism. Overall, the murabahah contract implementation in gold installment financing at BSI Pasuruan demonstrates strong adherence to sharia principles and serves as an effective financing solution for the community.